THE EFFECTIVENESS OF SNAKEHEAD FISH NUGGETS ON BODY MASS INDEX OF BREASTFEEDING MOTHERS - Julianto Laia, Tety N, Annisa Dwi, Nining Fitrianingsih, Tisna Yanti, Fajar Adhie, Ratih Suryaman, Anisya Fajar, Magdalena, Yuliana, Rahma (South Eastern European Journal of Public Health, 2025)
Introduction: Breastfeeding mothers represent a particularly vulnerable demographic when it comes to malnutrition. Weight loss in this group often correlates with a reduced Body Mass Index (BMI). Objectives: The aim of this study is to assess the effect of snakehead fish nuggets on the BMI of breastfeeding mothers. A preexperimental design was employed, specifically a one-group pretest-posttest approach. Methods: The study sample comprised 128 participants, selected through a quota sampling method. Data collection involved the use of observation sheets, microtoise/stature meters, and scales. Measurements of BMI (height and weight) were taken before and after the intervention on day 14. The data were analyzed utilizing the Wilcoxon signed-rank test. Results: The findings indicated that a significant effect of the snakehead fish nuggets on the Body Mass Index (BMI) of breastfeeding mothers. Conclusions: The study showed that there is a significant difference in BMI values in breastfeeding mothers before and after taking snakehead fish nuggets. Therefore, it is recommended that the Community Health Center provide routine education in their work area to help improving the nutritional status of breastfeeding mothers.